T-cadherin gene variants are associated with nephropathy in subjects with type 1 diabetes - Nicolas, Anthony; Mohammedi, Kamel; Bastard, Jean-Philippe; Fellahi, Soraya; Bellili-Muñoz, Naima; Roussel, Ronan; Hadjadj, Samy; Marre, Michel; Velho, Gilberto; Fumeron, Frédéric (Nephrology, dialysis, transplantation, 2017)
High plasma adiponectin levels are associated with diabetic nephropathy (DN). T-cadherin gene (CDH13) variants have been shown to be associated with adiponectin levels. We investigated associations between allelic variations of CDH13 and DN in subjects with type 1 diabetes. Two CDH13 polymorphisms were analysed in 1297 Caucasian subjects with type 1 diabetes from the 'Survival Genetic Nephropathy' (SURGENE) (n = 340, 10-year follow-up), 'Genesis France-Belgium' (GENESIS) (n = 501, 5-year follow-up for n = 462) and 'Génétique de la Néphropathie Diabétique' (GENEDIAB) (n = 456, 9-year follow-up for n = 283) cohorts. Adiponectin levels were measured in plasma samples from GENESIS and GENEDIAB cohorts. Pooled analysis of GENEDIAB and GENESIS studies showed that baseline plasma adiponectin levels were higher in subjects with established/advanced DN at inclusion (P < 0.0001) and in subjects who developed end-stage renal disease (ESRD) at follow-up (P < 0.0001). The minor allele of rs3865188 was associated with lower adiponectin levels (P = 0.006). rs11646213 [odds ratio (OR) 1.47; 95% confidence interval (CI) 1.18-1.85; P = 0.0009] and rs3865188 (OR 0.71; 95% CI 0.57-0.90; P = 0.004) were associated with baseline prevalence of established/advanced DN. These polymorphisms were also associated with the risk of ESRD (0.006 < P < 0.03). The association between rs11646213 (but not rs3865188) and renal function remained significant after adjustment for plasma adiponectin. In SURGENE, rs11646213 [hazard ratio (HR) 1.69; 95% CI 1.01-2.71; P = 0.04] and rs3865188 (HR 0.74; 95% CI 0.55-0.99; P = 0.04) were associated with risk of renal events (defined as progression to more severe DN stages). Plasma adiponectin levels are associated with the prevalence of DN and the incidence of ESRD in patients with type 1 diabetes. CDH13 polymorphisms are also associated with the prevalence and incidence of DN, and with the incidence of ESRD in these patients. The association between CDH13 and DN may be due to pleiotropic effects, both dependent and independent of plasma adiponectin levels.